Use of Lipid-Lowering Medications and the Likelihood of Achieving Optimal LDL-Cholesterol Goals in Coronary Artery Disease Patients. (25th July 2012) - Karalis, Dean G.; Victor, Brett; Ahedor, Lilian; Liu, Longjian
Abstract : Background . In clinical practice, most coronary artery disease patients are not achieving their recommend LDL-cholesterol goal of <70 mg/dL. Methods. We conducted a retrospective analysis of outpatient electronic health records and the most recent lipid profile, lipid-lowering medications and doses were collected. Results. We identified 9950 coronary artery disease patients. Only 37% on a statin alone achieved an LDL-cholesterol of <70 mg/dL, and most were on moderate-to-high-potency statins. The intensity of statin therapy did not improve LDL-cholesterol goal attainment. Among patients on combination therapy, 41% on statin plus ezetimibe and 46% on statin plus niacin achieved an LDL-cholesterol of <70 mg/dL (P = 0.01 and <0.0001 versus statin alone). If patients were switched to a high-potency statin LDL-cholesterol goal attainment of <70 mg/dL would increase to 46% and would increase up to 72% with combination therapy. Conclusions. Most coronary artery disease patients in clinical practice do not attain an LDL-cholesterol of <70 mg/dL, even among patients on high potency statins. The combination of statin plus either ezetimibe or niacin is the most effective regimen to achieve an LDL-cholesterol of <70 mg/dL, however, these drug combinations are used infrequently in clinical practice.